(A Look Back at) Go To Statement Considered Harmful. - Dijkstra, Edsger W. (Communications of the ACM, 2008)
The article presents a letter, originally published in 1968, assailing excessive use of the "go to" statement in computer programming. The author shares the view that a program's quality is inversely proportional to the number of "go to" statements it uses. "Go to" statements make programs messy and their use can be obviated by structured programming techniques. His opinion is informed both by experience and by the influence of persons such as Peter Landin, Christopher Strachey, and Heinz Zemanek. If he had his way the "go to" statement would be eliminated from all higher-level languages.